The Effects of Contemplative Education Process on Staff Well-being at Dansai Crown Prince Hospital, Loei Province - Inpalad, Anuchit; Prommawan, Siwaporn (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
This action research aimed to study the effects of contemplative education process on the happiness of personnel at Dansai Crown Prince Hospital in Loei Province, Thailand. The process integrated the seven basic principles of contemplative education with the cultural context and way of life of the community. The purposive sample consisted of 21 leaders and managers. The study was conducted from November 2023 to October 2024. Data were collected using the Happinometer, a tool for measuring staff happiness, before and after participating in activities, along with observations and reflections according to the action research process. Data were analyzed using descriptive statistics, including percentage, mean, standard deviation, and confidence interval, and inferential statistics using paired t-test. The results showed that after participating in the contemplative education process, the mean happiness score of personnel significantly increased from 3.32 to 4.02 (t = -8.453, df = 20, p < .001). Significant improvements were found in self-care, stress coping, work-life happiness, sense of meaning and value at work, emotional stability, and work inspiration. These findings align with the concept that happiness at work arises from both individual factors and organizational environmental factors that facilitate adaptation and balance. Developing a contemplative education process that aligns with the organizational context has the potential to significantly enhance the happiness and work efficiency of personnel in community hospitals. However, further long-term follow-up studies are needed to assess the sustainability of the changes.